Judge Schermer’s Top Ten Topics to Teach - Daniel Keating (Washington University Journal of Law & Policy, 2017)
This Article reviews the top topics under Chapter 11 bankruptcy reorganization Judge Schermer teaches to his law school students. Keating, a co-teacher of Judge Schermer’s for almost 30 years, compiled these topics from years of lecture notes, meetings, and observations of matters that excited Judge Schermer. The Author concludes that such topics under Chapter 11, including refusals to deal and the automatic stay, only cover a small fraction of Judge Schermer’s enthusiasm for teaching and bankruptcy law, with additional lists possibly needed to include other areas of his interest, such as consumer bankruptcy.
Keywords: Mentorship; Judge Schermer; Chapter 11 Bankruptcy; Automatic Stay; Bankruptcy Code; Post-petition Payments; Pre-petition Debt; Post-petition Loans; Creditor Committee; Executory Contracts; Bankruptcy Litigation; Bankruptcy Claims; Medical Benefits; Negative Amortization; Secured Creditors